Influence of physical fields upon adhesive strength of epoxy composite protective coatings in oil and gas sector - V.P. Kashytskyi, V.M. Malets (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2018)
The article investigates the influence of ultrasonic treatment and electromagnetic radiation on the adhesive strength of epoxy composite coatings in oil and gas sector, containing fine-particles. The results of research have been analyzed, optimal composition and type of treatment of epoxy polymer composition on the stage of formation have been selected. The introduction of high particle content ensures optimal significant improvement of study characteristics that indicate the future of research in this area and the feasibility of formation of high quality protective epoxy composite coatings.